On Iron Enrichment, Star Formation, and Type Ia Supernovae in Galaxy Clusters - Loewenstein, Michael (The Astrophysical journal, 2006)
The nature of star formation and SNe Ia in galaxies in the field and in rich galaxy clusters are contrasted by juxtaposing the buildup of heavy metals in the universe inferred from observed star formation and SN rate histories with data on the evolution of Fe abundances in the ICM. Models for the chemical evolution of Fe in these environments are constructed, subject to observational constraints, for this purpose. While models with a mean delay for SNe Ia of 3 Gyr and standard IMF are consistent with observations in the field, cluster Fe enrichment immediately tracks a rapid, top-heavy phase of star formation, although transport of Fe into the ICM may be more prolonged and star formation likely continues to redshifts <1. The source of this prompt enrichment is SNe II yielding .0.1 Mz-}per explosion (if the SN Ia rate normalization is scaled down from its value in the field according to the relative number of candidate progenitor stars in the 3-8 Mz range) and/or SN Ia explosions with short delay times associated with the rapid star formation mode. Star formation is >3 times more efficient in rich clusters than in the field, mitigating the overcooling problem in numerical cluster simulations. Both the fraction of baryons cycled through stars and the fraction of the total present-day stellar mass in the form of stellar remnants are substantially greater in clusters than in the field.